2023
DOI: 10.1063/5.0134959
|View full text |Cite
|
Sign up to set email alerts
|

Probing an enhanced anisotropy Seebeck coefficient and low thermal conductivity in polycrystalline Al doped SnSe nanostructure

Abstract: Recently, SnSe based thermoelectric materials attained much interest due to their environment friendly IV–VI semiconductor group. Herein, Al doped SnSe (Sn1−xAlxSe) specimens were prepared by combined ball milling and spark plasma sintering. High resolution transmission electron microscopy analysis of (Sn1−xAlxSe) nanostructure samples confirmed the existence of different crystal defects and dislocation induced by Al doping. Lower thermal conductivity (0.63 W/mK at 750 K) is observed for Sno.92Al0.08Se samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…It is therefore crucial to maintain the Bi 2 S 3 content below 1% to achieve an optimal thermoelectric performance in Ag 2 Se–Bi 2 S 3 composites. Notice that a similar evolution of the Seebeck coefficient with dopant concentration, first increasing and later decreasing at higher dopant concentrations, has been reported in other systems, and diverse mechanisms have been reported. Besides, previous studies have also shown increased Seebeck coefficients without affecting the electrical conductivity. The preserved electrical conductivity of Ag 2 Se after being mixed with Bi 2 S 3 is attributed to the notable increase in charge carrier mobility, which compensates for the moderate decrease in charge carrier concentration.…”
Section: Results and Discussionsupporting
confidence: 60%
“…It is therefore crucial to maintain the Bi 2 S 3 content below 1% to achieve an optimal thermoelectric performance in Ag 2 Se–Bi 2 S 3 composites. Notice that a similar evolution of the Seebeck coefficient with dopant concentration, first increasing and later decreasing at higher dopant concentrations, has been reported in other systems, and diverse mechanisms have been reported. Besides, previous studies have also shown increased Seebeck coefficients without affecting the electrical conductivity. The preserved electrical conductivity of Ag 2 Se after being mixed with Bi 2 S 3 is attributed to the notable increase in charge carrier mobility, which compensates for the moderate decrease in charge carrier concentration.…”
Section: Results and Discussionsupporting
confidence: 60%
“…29 After deconvolution, the binding energies of the Se 3d 5/2 and Se 3d 3/2 peaks are reported to be 53.7 and 54.7 eV, respectively. 30 Therefore, this result suggests the presence of Se 2− in the SnS 0.9 Se 0.1 :Ag pellet.…”
Section: ■ Introductionmentioning
confidence: 74%
“…The shift in the peak was caused by a change in bond length between Sn and Se after Zn doping, which resulted in a change in the equilibrium of nuclear geometry between the system's ground state and final ionized state. 44 The BE in Se 3d corelevel spectra (Figure 3b) of green pellets and pellets sintered at 200 °C is at 54.9 and 54.17 eV. These peaks correspond to SnSe 1+x and SnSe.…”
Section: Resultsmentioning
confidence: 96%
“…A slight shift toward the lower BE in the Sn 3d 5/2 orbital in Zn-doped pellets shows the substitution of Sn by Zn atoms. The shift in the peak was caused by a change in bond length between Sn and Se after Zn doping, which resulted in a change in the equilibrium of nuclear geometry between the system’s ground state and final ionized state . The BE in Se 3d core-level spectra (Figure b) of green pellets and pellets sintered at 200 °C is at 54.9 and 54.17 eV.…”
Section: Results and Discussionmentioning
confidence: 99%